Institution and Change on Community Access Right in Mangrove Forest Management in East Sinjai, South Sulawesi - Suharti, Sri; Darusman, Dudung; Nugroho, Bramasto; Sundawati, Leti (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2016)
ABSTRACTMangrove forests in Tongke-tongke is an example of success story of natural resources self governing. The research aims to describe the dynamic of local institution development and its effectiveness in mangrove management growing on accretion land in Tongke-tongke village, East Sinjai, South Sulawesi. This is a qualitative research by using case study method. The results showed that even without government support, collective action in mangrove management can be realized through various rules and agreements formulated collectively by local institution. Achievement of its management was evaluated by using design principles of Ostrom. Norms and rules agreed by the community has functioned as guideline in mangrove management following enforcement of sanctions for noncompliance. Accretion land under Act No. 16 of 2004 is state property but due to late support and government attendance has caused state property status becomes illegitimate. Ambiguity in tenurial status causing property typology of mangrove forests in East Sinjai can not be classified strictly. This then instigate multilayer property status for different types of products and services produced impying changes in access right to mangrove forest. The success of communities to manage mangrove sustainably in Eastern Sinjai should be supported with the provision of legal access to the public.Keywords: acccess right, accreting land, institution, mangrove, property status,ABSTRAKHutan mangrove di Tongke-tongke merupakan success story kemandirian masyarakat dalam melakukan pengelolaan sumberdaya alam secara lestari. Tujuan penelitian adalah untuk mendeskripsikan dinamika perkembangan serta efektivitas kelembagaan lokal dalam pengelolaan mangrove yang tumbuh pada tanah timbul di Desa Tongke-tongke, Sinjai Timur, Sulawesi Selatan. Penelitian ini merupakan penelitian kualitatif dengan metode studi kasus. Hasil penelitian menunjukkan bahwa walaupun tanpa dukungan pemerintah, aksi kolektif untuk menanam mangrove dapat diwujudkan melalui berbagai aturan dan kesepakatan yang dirumuskan secara kolektif melalui kelembagaan lokal yang dievaluasi menggunakan desain prinsip Ostrom. Norma dan aturan yang disepakati telah berperan menjadi patokan tindak masyarakat dalam menjaga tegakan mangrove berikut upaya penegakan sangsi bagi yang melanggar. Meskipun tanah timbul secara de jure menurut Undang-undang No 16 Tahun 2004 berstatus lahan negara (state property), namun negara yang terlambat hadir menyebabkan status state property menjadi tidak legitimate. Ambiguitas dalam status property menyebabkan tipologi property hutan mangrove di Sinjai Timur tidak dapat diklasifikasikan secara tegas sehingga menghasilkan status property yang berlapis (multilayer property) untuk berbagai jenis produk dan jasa yang dihasilkan yang kemudian berimplikasi pada perubahan hak akses masyarakat terhadap hutan mangrove. Keberhasilan masyarakat dalam mengelola mangrove secara lestari di Sinjai Timur perlu didukung dengan pemberian akses secara legal kepada masyarakat..Kata kunci: hak akses, kelembagaan, mangrove, status property, tanah timbul